EDUCATIONAL WEB-QUEST IN NEW INTERNET-EDUCATION ELECTIVE COURSES IN PHYSICS - Grabchak, Д.В. (Journal of Information Technologies in Education (ITE), 2012)
The article reveals the essence of the concept of "educational web-Quest" proved its application in the study of elective courses in physics, methodical advice for teachers on the design features of elective courses in physics through the use of educational web-quest.